Against Respecting Each Others' Differences. (7th August 2013) - Balint, Peter
Abstract: In contrast to multicultural theory, which in discussions of respect for difference has primarily focussed on the state as the agent of respect, multicultural policy has instead tended to focus on citizens themselves as the potential agents of this sort of respect. This article examines the plausibility of this type of respect (which is advocated by some theorists too), and argues that is not a reasonable or necessary demand. While there are several different ways of understanding respect — most of which focus on respecting persons — none seem capable of doing the work required for it to enable either the adequate or reasonable accommodation of diversity in a liberal society. More specifically, I use Darwall's influential distinction between appraisal and recognition respect — the latter in a broad non‐moralised sense — to make my case. While appraisal respect for difference may be theoretically easy to dismiss, it is not uncommon in multicultural policy. On the other hand, recognition respect — which is more behavioural than attitudinal — may appear a more plausible candidate. Yet it too remains overly demanding for individual citizens, especially, and most importantly, in difficult cases. I conclude that tolerance of difference (coming out of respect for citizenship) is a more appropriate demand on the individual.